Determination of α-tocopherol in cereal grains by use of saponification coupled with ionic-liquid-based dispersive liquid–liquid microextraction before high-performance liquid chromatography-mass spectrometry. Issue 26 (21st June 2016) - Xie, Qilong; Sun, Dekui; Cao, Jiangping; Jia, Litao; Hou, Bo; Li, Debao
Abstract : A selective and low organic-solvent-consuming method of sample preparation combined with high-performance liquid chromatography-mass spectrometry detection is introduced for the analysis of α-tocopherol in cereal grains. Abstract : A selective and low organic-solvent-consuming method of sample preparation combined with high-performance liquid chromatography-mass spectrometry detection is introduced for the analysis of α-tocopherol in cereal grains. The sample treatment involves initial saponification and preconcentration of the analyte performed by ionic-liquid-based dispersive liquid–liquid microextraction, with ethanol as disperser solvent and 1-octyl-3-methylimidazolium hexafluorophosphate as extraction solvent. The method offered excellent linearity over a range of 0.5–15 μg g −1 with a correlation coefficient of r > 0.998. Intra-day and inter-day repeatability, expressed as relative standard deviation were 3.4% and 5.9%, respectively. The quantitation limits and detection limits were 2.5 and 0.7 ng g −1 . Satisfactory recoveries ranging from 86.5% to 106.3% were obtained. The developed method was successfully applied to 12 cereal grain samples.